A systematic review of experimental studies investigating attitudes towards sexual revictimization: Findings, ecological validity, and scientific rigor. (July 2021) - Wager, Nadia M.; Goodson, Simon; Parton, Loren E.
Abstract: Background: Evidence from attrition studies indicates that complainants who experience sexual assault on more than one occasion and by different perpetrators (i.e. sexual revictimization) are unlikely to have their cases progress through to prosecution. Purpose: The aim of this systematic review was to ascertain what can be learned from experimental studies to aid the understanding of this real-world phenomenon. Specifically, to investigate the attributions made to hypothetical cases of sexual revictimization in mock-juror-type, (quasi)experimental studies. Methods: This systematic review entailed searching 13 electronic databases. Over 6000 potential sources were generated, of which 24 met the criteria for full-text reading. Application of the inclusion criteria, led to this review being based on 12 articles published between 1976 and 2020. These referred to 16 studies involving 4021 participants. Findings: The findings, except for one study, revealed consistent evidence of bias towards victims of sexual revictimization, which related to higher levels of disbelief and victim-blame, and other factors. Complainants were blamed most by women when the context was perceived as risky. Conclusions: There were several methodological issues with many of the studies which compromised their ecological validity and applicability. Recommendations are made for future research in this area, and police training and practice. Highlights: The findings demonstrate evidence of consistent bias against sexual assault complainants who are known to have made a previous allegation of sexual victimization. The finding holds true for both male and female victims, and revictimization that occurs in both childhood and adulthood. It also appears that women rather than men are more likely to express the bias In the real-world, bias typically manifests as disbelief and the labelling of reported sexual assaults as false allegations, yet most of the experimental research focuses on victim-blaming. Future research should attempt to understand the problem as it manifests in the real-world. That is, by creating vignette scenarios that truly reflect the problem, writing vignettes from the perspective that matches the most likely point of attrition, using meaningful and validated measures as dependent variables and selecting participant samples that match the age and gender composition of serving police officers or jurors.